A foucauldian autoethnographic account of a male former soccer player's move to coaching female players: a call to problematize the importation of gendered assumptions during a common coaching transition - Jones, L.; Avner, Z. (International Sport Coaching Journal, 2025)
It has frequently been observed that the disproportionate number of male coaches within women`s soccer is problematic, not least, because it limits the opportunities for the progression of female coaches. Despite this, the transition from "male former player to male coach of female players" is one that remains common, is likely to continue, yet is not widely discussed in the sport/coach transition literature. This is an oversight given the numerous problematic outcomes that are routinely connected to the presence of male coaches in women`s sport. In this confessional, analytical autoethnography, we build upon our existing work regarding coaching women`s soccer that has been informed by Michel Foucault`s conceptual framework. Precisely, we use a collection of creative narrative reflections to discuss the first author`s transition from that of a British semiprofessional soccer player context, to an Assistant Coach of a female soccer team in a North American varsity program. In so doing, we trace and map some of the (problematic) learned gendered assumptions which initially shaped and guided the first author`s coaching assumptions, relationships, approaches, and practices within this context, before unpacking some of the challenges he navigated along the way (with varying degrees of success). We end by summarizing our paper and a call to male coaches working with female athletes to reflect on how "thinking with Foucault" might help them to coach in more ethical and gender-responsive ways by both problematizing imported gendered assumptions and developing active allyship practices.